Health evaluation system, health evaluation method, and recording medium - SHINKAWA SATOSHI; NAKAMURA KEISUKE; SAKAI, HIDEKI; ONO HIROSHI; IMAI, TOMOHIRO; MITSUZAWA SHIGENOBU (2024)
The invention provides a health evaluation system, a health evaluation method, and a recording medium, which can properly determine the health state of a person using a moving body. A health evaluation system (1) is provided with: an acquisition unit that acquires a blood pressure value of a subject; and an evaluation unit that evaluates the health state of the subject on the basis of the acquired blood pressure value, and that evaluates the health state of the subject on the basis of a standing-time blood pressure value, which is a blood pressure value during movement of the subject toward the moving body in a standing state, and a seating-time blood pressure value, which is a blood pressure value of the subject after the subject is seated on the seat by multiplying the moving body. And evaluating the health state of the subject. 本发明提供健康评价系统、健康评价方法以及记录介质，适当地判断使用移动体的人的健康状态。健康评价系统(1)具备：取得部，其取得对象者的血压值；以及评价部，其基于取得的血压值来评价对象者的健康状态，评价部基于对象者在站立的状态下朝向移动体移动的中途的血压值即站立时血压值和乘上移动体并就座于坐席之后的对象者的血压值即就座时血压值，来评价对象者的健康状态。